2010
DOI: 10.1002/bip.21426
|View full text |Cite
|
Sign up to set email alerts
|

Segmental isotopic labeling of the Hsp70 molecular chaperone DnaK using expressed protein ligation

Abstract: Introducing biophysical labels into specific regions of large and dynamic multidomain proteins greatly facilitates mechanistic analysis. Ligation of expressed domains that are labeled in a desired manner before assembly of the intact molecular machine provides such a strategy. We have elaborated an experimental route using expressed protein ligation (EPL) to create an Hsp70 molecular chaperone (in this case the E. coli Hsp70, DnaK) where only one of the two constituent domains was labeled, in this case with NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…In Vivo Assays-Phage propagation and heat shock assays were performed as described previously using E. coli strain BB1553 transformed with plasmid pMS119-dnaK (13,25). In the ⌬secB assay with controllable dnaK expression, colonies of E. coli strain GP502 transformed with pMS119-dnaK plasmids were used to inoculate overnight cultures grown at 30°C in LB media supplemented with 0.5% arabinose, 50 mg/liter ampicil- (6,29,58), the NBD (green) is joined to the SBD (blue) through a short interdomain linker (red).…”
Section: Methodsmentioning
confidence: 99%
“…In Vivo Assays-Phage propagation and heat shock assays were performed as described previously using E. coli strain BB1553 transformed with plasmid pMS119-dnaK (13,25). In the ⌬secB assay with controllable dnaK expression, colonies of E. coli strain GP502 transformed with pMS119-dnaK plasmids were used to inoculate overnight cultures grown at 30°C in LB media supplemented with 0.5% arabinose, 50 mg/liter ampicil- (6,29,58), the NBD (green) is joined to the SBD (blue) through a short interdomain linker (red).…”
Section: Methodsmentioning
confidence: 99%
“…Although further optimization of the transpeptidation reactions under denaturing conditions is necessary to achieve optimal performance, the transpeptidation system developed in this study is poised to solve the previously reported problem of domain region spatial unavailability, which may limit the coupling reactions in certain cases [19].…”
Section: Discussionmentioning
confidence: 99%
“…As this result may be explained by the improved spatial availability of the termini of the domains being ligated [19], the primary objective of our work was to achieve efficient srtA-driven protein transpeptidation under denaturing conditions through protein modification.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmids encoding DnaK NBD(1-388) T199A, NBD(1-392)T199A, and NBD(1-393)T199A were prepared previously in our laboratory; they were expressed in E. coli and purified as described (3,37). 2 H-, 13 C-, and 15 N-labeled NMR samples were prepared using established protocols (38), as described previously (37) (see SI Text).…”
Section: Methodsmentioning
confidence: 99%